Penguatan Konsep Dasar Fisika Dengan Metode Pembelajaran Gasing Pada Siswa dan Guru MA Pondok Pesantren Aikmual Lombok Tengah NTB - Hiden - Hiden; Lily Maysari Angraini; Marzuki Marzuki; Susi Rahayu (Jurnal Pengabdian Magister Pendidikan IPA, 2020)
For a long period, some students in schools thought that Physics and Mathematics were difficult subjects. These two subjects are a scourge for students in most schools, not only in the NTB area but also in various other regions throughout Indonesia. For this reason, multiple efforts need to be made to overcome these learning difficulties. Learning Physics and Mathematics should emphasize providing direct experience to develop student competencies, directed to "find out" and "do" to help students gain understanding. It will be significantly easier for students if learning Physics and Mathematics invites students to learn to formulate concepts inductively, based on empirical facts, first through the inquiry method. Teachers are faced with the low necessary abilities of students. Not a few teachers have complained about their students' low abilities, especially in understanding the basic concepts of Physics and Mathematics. Many factors influence this, one of which is the input factor (students). Students from different schools have different levels of understanding, both in Physics and Mathematics. It is a fact that, in general, students who graduated from SMP / M.Ts. There are still many basic concepts of Physics and Mathematics which are relatively low. When comparing students who come from the city and out of town schools, public and private schools, they have quite significant differences in graduates' ability. This condition also contributes to the low quality of the input. Based on this condition, we hold community service activities to strengthen understanding of the basic concepts of Physics and Mathematics for students as their initial provision for studying other material in more depth. The approach used is an empirical approach with guided inquiry methods. The results obtained are that the learning method of this model is very popular with students and teachers, and with the help of Guided Inquiry-based worksheets, it is straightforward for students to improve their understanding of the basic concepts of physics and mathematics, because the guidance in the LKS is very structured.